Consumer Evaluations of Brand Extensions in An FMCG Sector - Dillu Koshy, Thomas (2010)
“Brand Extensions” are a vital element for a business and it has become a very common practice for the companies, especially in the FMCG sector to grow in its sales and profit targets. Although, how much ever advantages brand extension possess, it can still be of major risks in terms of brand dilution and its equity (Loken & John, 1993).